Diffuse phase transition and dielectric tunability of Ba(ZryTi1-y)O-3 relaxor ferroelectric ceramics - Chew, Khian Hooi; Chan, H.L.W.; Tang, X.G. (2004)
Barium zirconate titanate Ba(ZryTi1-y)O-3 (BZT, y = 0.2, 0.25, 0.30, 0.35) ceramics have been prepared by a sol-gel process. The temperature dependence of dielectric permittivity of the ceramics has been investigated. The results show that the phase transition temperature T-C (or T-m) is suppressed with increasing Zr content. The degree of diffuseness of the phase transition is more pronounced for higher Zr content, implying the existence of a composition-induced diffuse phase transition of the ceramics with 0.20 less than or equal to y less than or equal to 0.35. For BZT ceramics with y > 0.25, a relaxor ferroelectric characteristic is observed. High turtability and figure of merit are obtained in BZT compositions investigated, which imply that these ceramics are promising materials for tunable capacitor applications. (C) 2004 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.